Prairie Band Potawatomi Indians in Mayetta - Jackson County - McCollum, Patricia (Kansas State University, The Chapman Center for Rural Studies, 2013)
This study of persistence factors on an Indian reservation in Northeast Kansas includes interviews from Prairie Band Potawatomi Tribal Council member Carrie L. O’Toole (Wabaunsee), Prairie Band tribal member Laveda L.T. Wahweotten, and Dr. Eric Anderson of Haskell Indian Nations University. The study also includes recent maps of the Prairie Band Potawatomi Reservation, along with a photograph of the Prairie Band Potawatomi written language and an extension into the historical background of the Potawatomi Indian Tribes.
Patricia McCollum, “Prairie Band Potawatomi Indians in Mayetta - Jackson County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/134.
Keywords: Jackson County; Kansas; Mayetta; Potawatomi Indians; Pottawatomie County; Reservation